2017
DOI: 10.22159/ijcpr.2017v9i4.20978
|View full text |Cite
|
Sign up to set email alerts
|

Study on Immunostimulatory Property of Few Seaweeds Injected Intraperitoneally

Abstract: Objective: Three type of seaweed was chosen for the study namely Gracilaria corticata, Ulva lactuca and Stocheospermum marginatum and was extracted with ethanol. Methods:The fishes [Common carp (Cyprinus carpio) (weight 10±5g)] were divided into five groups. They were infected with A. hydrophila (1.6 × 10 4 CFU/fish). The infected three groups were injected with seaweed extract (0.20 mg) suspended in saline solution. One group was injected only saline control the other one group was injected with ciprofloxacin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…From the literature reports [19], it was confirmed that not much research work has been done regarding the bioactive compounds from Oedogonium intermedium. All the three solvent extracts viz., cold-and hot-water extracts and methanol extracts were made dry by suction and keeping in a hot air oven set at 50 ° C. They were then mixed with pre-warmed silica and introduced into three separate columns (first one packed with methanolic extract, a second column with hot aqueous and the third one with cold aqueous extract of Oedogonium intermedium), each charged with silica gel, 60-120 mesh (500 g) for chromatographic separation.…”
Section: Phytochemical Isolationmentioning
confidence: 98%
“…From the literature reports [19], it was confirmed that not much research work has been done regarding the bioactive compounds from Oedogonium intermedium. All the three solvent extracts viz., cold-and hot-water extracts and methanol extracts were made dry by suction and keeping in a hot air oven set at 50 ° C. They were then mixed with pre-warmed silica and introduced into three separate columns (first one packed with methanolic extract, a second column with hot aqueous and the third one with cold aqueous extract of Oedogonium intermedium), each charged with silica gel, 60-120 mesh (500 g) for chromatographic separation.…”
Section: Phytochemical Isolationmentioning
confidence: 98%
“…Different food types including herbs have been tested for better growth and immunity of ornamental fish industry (Madhusudan et al, 2011;Radhika and Mohaideen, 2017). Production of costeffective nutritionally balanced diets of fish is the main factor affecting intensive aquaculture due to its influence on growth, health and production cost (Yeşilayer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%